ปัญหาการใช้หลักสูตรการศึกษาขั้นพื้นฐาน พุทธศักราช 2544 ของครูผู้สอนกลุ่มสาระการเรียนรู้สุขศึกษาและพลศึกษา ในโรงเรียนนำร่อง - เพ็ญนภา ไพรบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study and compare the problems on implementation of Basic Education Curriculum B.E. 2544 among teachers in health and physical education subject group in pilot schools. The sampling groups were categorized into 3 different major subject groups, they were health, physical education and other major subject group. The questionnaires constructed by the researcher were sent to the 324 respondents and 266 questionnaires were returned which accounted for 82.08%. The data were then analyzed by means of percentages, means, standard deviation. One-way analysis of variance and Scheffe test were also applied to test group differences at .05 level. The findings were as follows: 1. The problems of the teachers in health and physical education subject group on implementation Basic Education Curriculum B.E. 2544 were found at the moderate level in 3 areas : the learning media, the teachers themselves, and the knowledge and understanding of the curriculum structure materials. However, the learning porcess managements and the measurement snd evaluation were found at the low level. 2 The comparison of the problems on implementation of Basic Education Curriculum B.E. 2544 among teachers in three different major subject groups was found statistically significant differences at .05 level. The teachers in health education major subject group had the most problems while the group of the teachers in physical education major subject group had the least problems.